Life Cycle Assessment of a Bicycle Using Solidworks Sustainability - Bin Kasmer, MOHAMAD YUSOFF IMRAN; Ts. Dr. Fahrul Bin Hassan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
According to a case study, the life cycle assessment of bicycles today can be seen as various types of city bicycles that do not follow the procedure of design structure, that bicycles are not compatible and give effect to sustainability in terms of material use and the process involved, which can lead to environmental impact. Other examples include bamboo bicycles, which are cost-effective and innovative but not sustainable if mass-produced in large quantities. In terms of the product’s manufacturing stage, processes such as process welding, extrusion, drilling, and others should be considered. The objective of this project is (1) To use SolidWorks sustainability analysis to evaluate a bicycle’s entire lifecycle (cradle-to-grave analysis). (2) To determine which bicycle components have the greatest environmental impact. (3) To reduce the environmental impact of the component identified in (2) by improving its design. This study is being carried out to provide an understanding of life cycle assessment using SolidWorks software in the section of sustainability in comparison to current bicycle products. The process of analyzing design structure through the use of software tools. There are a variety of approaches that have been used to introduce undergraduate students to sustainability and life cycle assessment concepts, ranging from demonstrations to specialized courses. The selection of design is a component of a bicycle that can be put through its paces, similar to a traditional technique for introducing students to CAD software. In this part, we focused on the assessment of environmental impact and eco-sustainability of models created with CAD SolidWorks software. We assessed the material used to build the entire assembly in terms of efficiency, reliability, and environmental pollution, taking into account the carbon footprint, energy consumption, air acidification, and eutrophication. The best solution for this objective is the wooden oak where the material can reduce the environmental impact and also the convenient financial sector. Lastly, The analysis of the sustainability of Solid works is the beginning of the solution of this project and needs to be improved in sustainability tools to evaluate more complicated design and materials. During the construction of the project, one of the recommended needs to apply the project is to have the bicycle design based on a real company. This is because the analysis of sustainability is more realistic to environments. Another recommendation is that selected materials need to be more specific to the component part of the design like skew, net, bolt, the special component part, etc.